2008
DOI: 10.1073/pnas.0708460105
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic shifts in solid-state NMR of proteins to elicit structural information

Abstract: The recent observation of pseudocontact shifts (pcs) in 13 C highresolution solid-state NMR of paramagnetic proteins opens the way to their application as structural restraints. Here, by investigating a microcrystalline sample of cobalt(II)-substituted matrix metalloproteinase 12 [CoMMP-12 (159 AA, 17.5 kDa)], it is shown that a combined strategy of protein labeling and dilution of the paramagnetic species (i.e., 13 C-, 15 N-labeled CoMMP-12 diluted in unlabeled ZnMMP-12, and 13 C-, 15 N-labeled ZnMMP-12 dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
144
1
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(150 citation statements)
references
References 49 publications
3
144
1
2
Order By: Relevance
“…It should be noted that although only C α PCSs are plotted in this figure, the fittings of the Δχ tensor parameters use all 13 C and 15 N PCSs. 36 in which they observed consistent PCSs in solid and solution state when the paramagnetic metal ions are in an internal, nonsolvent-exposed environment. Their observations reflect the similar local chemical environment around the paramagnetic metal ions in the solid and solution states.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…It should be noted that although only C α PCSs are plotted in this figure, the fittings of the Δχ tensor parameters use all 13 C and 15 N PCSs. 36 in which they observed consistent PCSs in solid and solution state when the paramagnetic metal ions are in an internal, nonsolvent-exposed environment. Their observations reflect the similar local chemical environment around the paramagnetic metal ions in the solid and solution states.…”
mentioning
confidence: 76%
“…These advantageous properties of PCS-based approach are expected to accelerate the structure determination of the proteins by solid-state NMR. Indeed, previous studies of PCSs in a metalloprotein 36 have shown great potential of PCSs as a source of long-range restraints for structure determination by solid-state NMR.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
See 1 more Smart Citation
“…These effects act up to very long distances, and carry a well-defined dependence on the nuclear position with respect to the paramagnetic center. In solids, measuring pseudocontact shifts is relatively straightforward, and when they occur, they can be used as invaluable structural constraints (20)(21)(22). However, measuring PREs in solids is a prime example where traditional detection methods have difficulty to provide sufficient sensitivity.…”
mentioning
confidence: 99%
“…In recent years, several experimental approaches have been proposed to overcome these intrinsic difficulties both in static solids and under magic-angle spinning (MAS) conditions [2][3][4]. Investigations of systems containing paramagnetic centers have proved to be important for a variety of fields, ranging from the structure determination of metalloproteins [5][6][7][8] to the characterization of catalytic organometallic complexes [9][10][11][12][13][14]. We have recently shown that spin-echo techniques based on combs of rotor-synchronized pulses employing Delays Alternating with Nutation for Tailored Excitation (DANTE) [15][16][17][18] can be used to excite nuclei such as protons that experience severe inhomogeneous broadening due to nearby paramagnetic nuclei [19].…”
Section: Introductionmentioning
confidence: 99%